Correction: Additive Function of Vibrio vulnificus MARTX Vv and VvhA Cytolysins Promotes Rapid Growth and Epithelial Tissue Necrosis During Intestinal Infection. - Hee-Gon Jeong; Karla J F Satchell (PLoS Pathogens, 2019)
[This corrects the article DOI: 10.1371/journal.ppat.1002581.].